Pengaruh Pengetahuan Kewirausahaan, Motivasi Berwirausaha, E-Commerce, dan Lingkungan Keluarga Terhadap Minat Berwirausaha Pada Mahasiswa Prodi Akuntansi Universitas Nusantara Pgri Kediri - Firnanda, Vira Erna; Widiawati, Hestin Sri; Kurniawan, Andy (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
An interest in entrepreneurship often comes to a person just like that. However, this interest can be influenced by several factors, both external and internal factors. The aim of this research is to determine the influence of entrepreneurial knowledge, entrepreneurial motivation, e-commerce, and family environment on students' interest in entrepreneurship. The research method used is quantitative with a comparative causal nature. The research population used in this research were students of the Nusantara University PGRI Kediri Accounting study program class 2018-2023 using the sampling method, namely using the Slovin formula. The sample size in this study was 122 respondents and was collected through a questionnaire. Data obtained Data was collected through questionnaires and includes primary and secondary data. Validity test, reliability test, classical assumption test, coefficient of determination test, and hypothesis test are used in data analysis. The results of this study show that entrepreneurial knowledge (X1) has a significant effect on interest in entrepreneurship, entrepreneurial motivation (X2) has a significant effect on interest in entrepreneurship, e-commerce (X3) has no effect on interest in entrepreneurship, and family environment (X4) has a significant effect on interest in entrepreneurship. Based on the results of the analysis and conclusions, the suggestions that the author can convey are as follows: for future researchers, this can be used as a guide to determine the influence of interest in entrepreneurship and try to use other variables besides the variables used in this research, especially variables that are similar to e-commerce variables.